2017
DOI: 10.1136/bmjopen-2016-013455
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to major roads, exposure to fine particulate matter and aortic calcium: the Framingham Heart Study, a cohort study

Abstract: ObjectivesTraffic and ambient air pollution exposure are positively associated with cardiovascular disease, potentially through atherosclerosis promotion. Few studies have assessed associations of these exposures with thoracic aortic calcium Agatston score (TAC) or abdominal aortic calcium Agatston score (AAC), systemic atherosclerosis correlates. We assessed whether living close to a major road and residential fine particulate matter (PM2.5) exposure were associated with TAC and AAC in a Northeastern US cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
2
10
1
Order By: Relevance
“…Indeed, in our study participants with a higher TAC at baseline had higher incidences of cardiovascular-related mortality, as well as higher rates of incident statin medication. Although air pollution exposure may contribute more to the development of early soft plaque than to progression to arterial calcification, 15 which is in line with results from our prior analysis of second-hand smoke and CAC in the Heinz Nixdorf Recall study, 30 negative associations remain to be explained. In line with our previous cross-sectional investigation 17 and results from a recent review, 5 air pollution and noise revealed independent health effect estimates.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Indeed, in our study participants with a higher TAC at baseline had higher incidences of cardiovascular-related mortality, as well as higher rates of incident statin medication. Although air pollution exposure may contribute more to the development of early soft plaque than to progression to arterial calcification, 15 which is in line with results from our prior analysis of second-hand smoke and CAC in the Heinz Nixdorf Recall study, 30 negative associations remain to be explained. In line with our previous cross-sectional investigation 17 and results from a recent review, 5 air pollution and noise revealed independent health effect estimates.…”
Section: Discussionsupporting
confidence: 79%
“…While a linear exposureresponse for PM 2.5 (aerodynamic diameter 2.5 mm) and the progression of CAC was observed in the prospective Multi-Ethnic Study of Atherosclerosis (MESA) cohort, 13 the analysis of the Framingham Study did not support associations of living close to a major road or PM 2.5 exposure with the presence or extent of CAC, TAC or AAC progression. 15,16 Road traffic noise has rarely been investigated in the context of air pollution and our previous cross-sectional investigation supported independent associations of air pollution and noise on TAC. 17 However, it remains unclear whether high air pollution exposure enhances the effect of noise on the cardiovascular system and vice versa.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…These findings are in line with investigations based on the Framingham Heart Study, which also found null or inverse estimates in analyses of participants with apparent calcifications at baseline ( Dorans et. al 2016 , 2017 ). One explanation for inverse associations in participants with advanced atherosclerosis at baseline could be the dominating effect of cardioprotective therapy, which is more common in participants with advanced atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are in line with investigations based on the Framingham Heart Study, which also found null or inverse estimates in analyses of participants with apparent calcifications at baseline -53:9 ± 9:4 5 3 :8 ± 9:4 5 3 :9 ± 9:3 5 3 :9 ± 9:3 Distance to highly trafficked road (m) -1,018:0 ± 808:7 1,033:2 ± 817:2 1,023:7 ± 811:3 1,025:5 ± 818:4 (Dorans et. al 2016(Dorans et. al , 2017.…”
Section: Discussionmentioning
confidence: 99%